Perancangan dan Implementasi Intelligence Human Capital Development Plan untuk Jabatan Fungsional Kepegawaian - Dita Nurmadewi; Elin Cahyaningsih; Randi Sunardi; Akbarnama Tangguh Dipantara (JSAI (Journal Scientific and Applied Informatics), 2025)
Effective human resource management is an important key to improving organizational performance, especially in the government sector such as the State Civil Service Agency (BKN). This research focuses on the development of a website-based Intelligent Human Capital Development Plan (IHCDP) that utilizes the latest information technology, including PHP, JavaScript, and SQL, to dynamically identify, analyze, and meet employee training and development needs based on integrated data performance and training needs. The approach used in this study is the waterfall method, where each stage from design to implementation is carried out regularly and in a structured manner. The developed system allows real-time visualization of employee performance data, as well as analysis of training needs needed to improve employee competency in accordance with BKN's strategic objectives. The results of this study indicate that the implementation of IHCDP at BKN can increase efficiency in identifying specific training needs, aligning competency development with organizational goals, and significantly strengthening employee capacity in facing changes and challenges in the work environment. The use of information technology in this system also encourages the creation of transparency and accountability in human resource management in the BKN environment. Recommendations for developing features can later be developed into a dashboard to view the history of competency results carried out every two years at each level of office.